2023
DOI: 10.3389/fimmu.2023.1221125
|View full text |Cite|
|
Sign up to set email alerts
|

Modifiable risk factors linked to the development of rheumatoid arthritis: evidence, immunological mechanisms and prevention

Jeba Atkia Maisha,
Hani S. El-Gabalawy,
Liam J. O’Neil

Abstract: Rheumatoid Arthritis (RA) is a common autoimmune disease that targets the synovial joints leading to arthritis. Although the etiology of RA remains largely unknown, it is clear that numerous modifiable risk factors confer increased risk to developing RA. Of these risk factors, cigarette smoking, nutrition, obesity, occupational exposures and periodontal disease all incrementally increase RA risk. However, the precise immunological mechanisms by which these risk factors lead to RA are not well understood. Basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 223 publications
0
2
0
Order By: Relevance
“…RA is mostly caused by interaction of genetic and environmental factors [4][5][6]. Other risk factors include age, gender and environmental exposure i.e., smoking, different air pollutants and infectious agents [7,8]. RA is typically classi ed into two types seropositive or seronegative.…”
Section: Introductionmentioning
confidence: 99%
“…RA is mostly caused by interaction of genetic and environmental factors [4][5][6]. Other risk factors include age, gender and environmental exposure i.e., smoking, different air pollutants and infectious agents [7,8]. RA is typically classi ed into two types seropositive or seronegative.…”
Section: Introductionmentioning
confidence: 99%
“…). Studies have identified periodontitis as a modifiable risk factor of rheumatoid arthritis ( 9 ), the treatment of which is strongly associated with a reduction of inflammatory parameters( ( 10 ), Peng et al. , Gao et al.…”
mentioning
confidence: 99%